The place of work diagnostic instrumental measurements in the protocols of occupational health tasks (Belügyi Szemle, 2024)
Aim: Work diagnostic examinations are carried out to assess aptitude, job selection, pre-rehabilitation assessment and follow-up, career guidance. Work diagnostic tests include aptitude tests, various questionnaires, work practice tests and instrumental examinations. For instrumental testing, portable work psychology testing instruments or so-called ‘work-simulators’ can be used. Work simulators have been used for selection, assessment of aptitude, training for jobs requiring a high level of attention and with an increased risk of accidents.In the author’s opinion, work diagnostic instrumentation, work simulator tests (e.g. ErgoScope) can be well integrated into the protocol of primary and specialised occupational health care tasks.Methodology: The author conducted an online questionnaire survey among occupational health specialists working in Hungary to find out whether they use work diagnostic tools, and if so, which ones, and whether they would be willing to send workers for instrumental work diagnostic tests. 272 second-level medical fitness for work examinations were reviewed for their inclusion in the instrumental work diagnostic tests.Findings: It is clear from the questionnaire responses that very few occupational health specialists have the opportunity to use occupational diagnostic instrumentation in their work, but 60.62% of them would be happy to send patients for instrumented skills testing. From the documentation of the second level medical fitness for work examinations, the author selected those where aptitude tests had been carried out and those where an instrumental aptitude test would have assisted the assessment.Value: It can be concluded that, in addition to the second level occupational/professional medical fitness tests, instrumental occupational diagnostic tests could be easily integrated into the examination protocols of occupational health, in the first level occupational/professional medical fitness tests, in career counselling and in the occupational rehabilitation process, and would significantly assist the work of occupational health professionals.